NUMERICAL SIMULATION OF THE 7 FEBRUARY 1963 TSUNAMI IN THE BAY OF CORINTH, GREECE - Lobkovsky L.I.; Mazova R.Kh.; Garagash I.A.; Kataeva L.Yu. (My University, 2006)
The paper addresses the event that occurred in the Bay of Corinth, Greece, on 7 February 1963. The tsunami was produced by a submarine landslide in the mouth of the local Salmenikos River. The paper presents preliminary numerical results obtained in terms of an elastoplastic model for the surface water waves generated by the landslide and propagated onto the coast. The wave propagation is analyzed as a function of the landslide movement. The inferred results are compared with those obtained in terms of other models.
Keywords: TSUNAMI GENERATION; SHALLOW WATER EQUATIONS; ASEISMIC TSUNAMI; SEDIMENTARY MASS